Analysis Regional Vulnerability of Earthquakes Based on Parameters Fragility Rock Value (B-Value) and Peak Ground Acceleration (PGA) In Bali Province - Lestari, Amalia Dwi; Suarbawa, Komang Ngurah; Supardi, I Wayan; Pratama, I Putu Dedy (BULETIN FISIKA, 2021)
Abstract - Bali is an area that is prone to earthquake hazards. This is because Bali is flanked by two causes of earthquakes, namely a subduction zone in the south and a back arc fault in the north. One of the efforts to minimize damage or loss caused by earthquakes is to analyze the vulnerability of an area to earthquakes. In this study, the earthquake parameters used as hazard indicators were the level of rock fragility (b-value) and maximum ground acceleration (PGA). Based on the results of the b-value calculation using the Maximum Likelihood method, the rock fragility level for the Bali region is obtained from 0.370 to 1.419. While the results of the PGA calculation using two empirical methods, namely the empirical M.V. Mickey and Lin Wu's empirical method is known that the empirical method of M.V. Mickey is more suitable for use in the Bali area than Lin Wu's empirical method, with PGA values ??ranging from 517.32-828.58 gal. So based on the results of the analysis of the two earthquake parameters, it is found that the area of ??Bali that is vulnerable to earthquakes is the western part of Buleleng Regency and most of Jembrana Regency. Keywords: b-value, PGA, Maximum Likelihood, M.V. Mickey, Lin Wu, Bali